2000
DOI: 10.1016/s0955-3959(00)00067-0
|View full text |Cite
|
Sign up to set email alerts
|

Doing the possible: harm reduction, injecting drug use and blood borne viral infections in Australia

Abstract: Most surveys show that, other than among men who inject drugs and have a history of homosexual contact, the prevalence of HIV infection among injecting drug users (IDUs) in Australia is about 2%. Rates of needle sharing have also declined greatly in the last decade, although the high prevalence and incidence of hepatitis C infection suggest that existing strategies have not yet brought this epidemic under control.Harm reduction has been the major Australian approach to the reduction of blood borne viral inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Recent research by Anderson et al (2000) reported that just 7% of IDUs attending a Sydney sexual health clinic had been vaccinated against HBV [32]. Loxley reported that only half of IDUs surveyed in Perth were aware of the existence of HBV vaccination [33].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research by Anderson et al (2000) reported that just 7% of IDUs attending a Sydney sexual health clinic had been vaccinated against HBV [32]. Loxley reported that only half of IDUs surveyed in Perth were aware of the existence of HBV vaccination [33].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they are again becoming a reservoir for transmitting HIV to other segments of the population. Scientific studies have demonstrated the effectiveness of harm minimization programs (Loxley, 2000). Nevertheless, the pragmatic approach that effectively curbed heterosexual transmission via commercial sex, which is also illegal in Thailand, has not yet been adopted.…”
Section: Develop Pragmatic Approaches To Reduce Transmission By Idusmentioning
confidence: 99%
“…In spite of successful demonstrations of HIV interventions for drtig users in Asia, current interventions are unlikely to be effective due to several factors. Implementation of effective policies and strategies early on in the epidemic can keep HIV at significantly low levels even in presence of injecting practices (Loxley 2000), and the incidence of HIV can be reduced (Peters et al 1998), showing thereby that prevention of drug-related HIV is feasible. Characteristics of effective HIV prevention interventions include early introduction of intervention (ideally before HIV is reported among the IDU population), availability of needle and syringe exchange programmes (NSP), and drug treatment programmes such as methadone substitution and outreach with active partnership by the drug user community.…”
Section: Critical Issues Relating To Interventions Among Idusmentioning
confidence: 99%